Cor, retrato e identidade : Humanae, o olhar sobre si e sobre o outro na obra de Angélica Dass - Wandekoken, Bruna (2017)
To think photography as an instrument or tool to discovery, affirmation or comprehension of identity. The act of verifying the portrait as a painting of gender has been influenced and modified through time by the use of photography, and how these two aspe